Morphodynamic regime change in a reconstructed lowland stream - J. P. C. Eekhout; R. G. A. Fraaije; A. J. F. Hoitink (Earth Surface Dynamics, 2014)
With the aim to establish and understand morphological changes in response to channel reconstruction, a detailed monitoring plan was implemented in a lowland stream called Lunterse Beek, located in the Netherlands. Over a period of almost 2 years, the monitoring programme included serial morphological surveys, continuous discharge and water level measurements, and riparian vegetation mapping, from photographs and field surveys. Morphological processes occurred mainly in the initial period, before riparian vegetation developed. The initial period was largely dominated by upstream sediment supply, which was associated with channel incision upstream from the study area. Herbaceous vegetation started to develop approximately 7 months after channel reconstruction. The monitoring period included two growing seasons. A clear increase of riparian vegetation cover from first to the second year was observed. Detailed morphological and hydrological data show a marked difference in morphological behaviour between the pre-vegetation and post-vegetation stage. A linear regression procedure was applied to relate morphological activity to time-averaged Shields stress. In the initial stage after channel reconstruction, with negligible riparian vegetation, channel morphology adjusted, showing only a weak response to the discharge hydrograph. In the subsequent period, morphological activity in the channel showed a clear relation with discharge variation. The two stages of morphological response to the restoration measures may be largely associated with the upstream sediment supply in the initial period. Riparian vegetation may have played a substantial role in stabilizing the channel banks and floodplain area, gradually restricting the morphological adjustments to the channel bed.